IDENTIFY ROLE OF LEARNING STYLE TOWARDS STUDENTS' COGNITIVE ACHIEVEMENT AND CREATIVITY ON OPTICS INSTRUMENT CONCEPT - Yufitri, Novi (2014)
Learning style is the way how student perceive, gather and process the information.VARK (Visual, Aural, Read/Write, and Kinesthetic) is one of the modality of learning style based on sensory modaliities. This research had been investgated the impact of learning style towards students' cognitive achievement and creativity on optic instrument concept. The method which is used in this research was weak experiment with one-group-pretest-posttest design. The sample was taken Randomly (n=33students) at grade 8 in Boarding School. The quantitative data of this research was gained through objective test of multiple question, while the qualitative data was gathered through rubrics. The result of this research found that there is a differences within group of learning style with significanty level 0.003. Thus, the creativity stdent who choose a project which is suitable with their learning style was obtained high score. This indicated that learning style has an role towards cognitive achievement and creativity on optic instrument concept.